Formal-semantic paradigm of the word bash/bosh ‘head’, ‘beginning’ in turkic languages - Boris A., Musukov; Fatimat P., Erkenova (Kavkazologiya, 2024)
The article is devoted to a multi-aspect study of the functional-semantic features of stock units of morphology of varying complexity, formed with the help of the polysemantic noun bash/bosh in various phonetic variants, known in Turkic languages for its usage since ancient times, since the monuments of ancient Turkic writing. The work analyzes idioms of phraseological type, formed as a result of the loss of compo-nent meaning by free phrases. It examines elliptical shapes formed in the process of losing the word bash/bosh form 3 l. units h. The phonetic feature of the word bash/bosh in the Turkic lan-guages is that they all retain a single form, except for Uzbek. The article draws attention to the features of selective combination of syntactic construc-tions with the word bash/bosh with inventory units of morphology.